2013
DOI: 10.31729/jnma.1944
|View full text |Cite
|
Sign up to set email alerts
|

Gross corelation between waist hip ration and random blood sugar level in Thami tribe of Dolakha district in Nepal

Abstract: Introduction:  Diabetes is one of the major public health problems in Nepal. Very few studies on correlation between waist hip ratio and random blood sugar have been done in remote areas of Nepal particularly in minor ethnic groups like Thami. This study attempted to compare waist hip ratio and blood sugar level in Thami community of Nepal.Methods: This cross sectional study was conducted in sub-health post of Lapilang village of Dolakha district of Nepal. A total of 243 local inhabitants from Thami Tribe part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
0
3
2
Order By: Relevance
“…The results of this study were not in line with previous research, which found that there was a relationship between waist-hip ratio and BGL [6,25]. These differences may be due to differences in the age groups, as age differences might determine body composition, which affects the distribution of muscle mass and total body fat [23,26]. A majority of the patients in this study were within the age of 46-55 years, while previous studies recruited younger patients.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The results of this study were not in line with previous research, which found that there was a relationship between waist-hip ratio and BGL [6,25]. These differences may be due to differences in the age groups, as age differences might determine body composition, which affects the distribution of muscle mass and total body fat [23,26]. A majority of the patients in this study were within the age of 46-55 years, while previous studies recruited younger patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies showed that there was a positive correlation between upper arm circumference and BGL in diabetic patients [19][20][21][22]. This might be due to differences in the selection of cut-off points in this study, making the result different from previous studies [23,26].…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Hip and waist circumference was assessed as described by Kharal et al [ 27 ]. Body mass was assessed by weighing the participant.…”
Section: Methodsmentioning
confidence: 99%